Scientific Literacy Skills through Palm-Oil–Based Contextual Science Learning Materials for Eighth-Grade Students - Jasri Jasri; Insih Wilujeng; Susilowati Susilowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study investigates the scientific literacy skills of eighth-grade students through palm-oil–based contextual science learning in a junior high school located near a palm oil plantation area. A descriptive qualitative approach was employed with 40 students as research participants, and data were collected through a science literacy test based on the PISA 2025 Science Framework. The results show that students’ scientific literacy falls within the medium category across three domains: explaining scientific phenomena (50.2%), constructing and evaluating scientific investigations (45.30%), and using scientific information for decision-making and action (45.68%). Interview and documentation data support these findings, indicating that students are able to relate science concepts to real-world contexts but face challenges in inquiry skills, experimental design, and interpreting scientific evidence. The results also align with previous studies reporting that scientific literacy among Indonesian middle school students remains limited due to memorization-oriented learning, limited exposure to inquiry activities, and inadequate contextualization of science instruction. These findings imply the need for ethnoscience-based and inquiry-driven learning that integrates local potential—such as palm oil plantation phenomena—to foster students’ conceptual understanding, investigative competence, and evidence-based decision-making